Durability of bonded FRP-to-steel jointsEffects of moisture, de-icing salt solution, temperature and FRP type - Heshmati, Mohsen; Haghani Dogaheh, Reza; Al-Emrani, Mohammad (Composites. Part B, Engineering, 2017)
This paper investigates the effects of environmental ageing on the mechanical response of adhesively bonded double-lap shear joints made of steel and CFRP or GFRP adherents. One hundred and ninety-two specimens, 84 joints and 108 material coupons, were aged for up to three years in various environments including (i) immersion in distilled water at 20 °C and 45 °C, (ii) immersion in de-icing salt solution at 20 °C and 45 °C and (iii) exposure to 95% relative humidity at 45 °C. In general, immersion at 45 °C resulted in noticeably greater strength reductions at both material and joint level. While the strength and stiffness of the joints made of GFRP material underwent significant reductions, the CFRP/steel joints were affected to a considerably smaller degree. FE simulations showed the impact of the permeability of FRP adherents and moisture distribution at the FRP/adhesive interface on the integrity and strength of the joints. The joint-level results are compared with the most relevant durability data in the literature.